Ethnicity, N. 9 : Ethnic Diversity and Ethnic Studies - (:unkn) unknown (Daugavpils Universitātes Sociālo pētījumu institūts, Latvijas Universitātes Filozofijas un socioloģijas institūts, 2013)
The articles published in this issue analyse the topic of ethnic diversity concerning the field of ethnic studies.
"Ethnicity" – a peer-reviewed journal was established by the Institute of Philosophy and Sociology (University of Latvia). The journal publishes original works about ethnicity in different fields of knowledge – sociology, history, social linguistics, social psychology, law, political science.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Ethnology; ethnic minority; ethnolinguistic vitality; Roma identity; «A New Book on Latvian Ethnopsychology» - book review